(untitled) (Journal of Population and Development, 2022)
This paper is based on level, trends and pattern of female labor migration in Nepal. The changes in the lives of Nepalese women due to the increasing trend foreign labor migration of men. The changes in intra-household power relations and the transformations in women’s lives, due to the male-dominated nature of Nepalese migration, are largely neglected. The aim of this paper to find the level and trend of female labour migration in Nepal and also examine women’s experiences, as they assume the role of household heads, financial managers and single parents, in a society that has historically suppressed their freedom. The analysis is based on secondary data source. Women who take on the role of household head are more likely to gain decision-making power and experience an increase in social participation, while those left under the supervision of other members (usually their in-laws) may suffer from reduced decision-making ability and increased restrictions on their mobility in public spaces. These consequences are highly sensitive to the regional socio-cultural norms as well as women’s caste, class, and individual characteristics. The consequences of female migration increasing trend day by day and their experience provides the valuable information for the developing policy of migration as well as traditional gender inequality and providing women with the resources to manage with the challenges faced during men’s migration.